Клиничка дијагностичка вредност нових серумских маркера липазе Ф, гастрина 2 и Кс-типа колагена α1 ланца код карцинома желуца: Serum markers lipase F, gastrokine 2 and the collagen X-type α1 chain in gastric cancer - Wang, Fashe; Li, Bai; Li, Shangyin; Tang, Yan; Tan, Tao (Journal of Medical Biochemistry, 2025)
Objective: To explore the application value of three novel serum markers, collagen X-type α1 chain (COL10A1), gastrokine 2 (GKN2), and lipase F (LIPF), in the diagnosis of gastric cancer. Methods: Differential markers of gastric cancer were mined from public databases (TCGA, GTEx). From November 2022 to October 2024, 108 healthy people and patients with stomach cancer who had gastroscopies and pathological examinations at our hospital were chosen to serve as research subjects. Of these, 60 patients had stomach cancer (28 in the early gastric cancer group and 32 in the advanced gastric cancer group), while 48 patients were in the healthy group. Receiver operating characteristic (ROC) curves were created in order to examine the relationship between the detection of gastric cancer and the serum levels of markers. Additionally, the application value of both the detection of new markers and the detection of conventional markers (PGI, PGII) in the diagnosis of gastric cancer was examined. Results: Three differential markers of gastric cancer (COL10A1, GKN2 and LIPF) were mined from a public database. By detecting the levels of three markers in clinical blood samples, AUC of the combined detection of the three markers (COL10A1+GKN2+LIPF, 3MP) in differentiating group (3MP vs PGR: 0.842 vs 0.841) and the early gastric cancer group (0.877 vs 0.843) was greater than that of PGR (PGI/PGII). The combined conventional markers (PGI, PGII) and the combined detection of five markers (3MP+PGI+PGII, 5MP) had AUCs of 0.963 and 0.953, respectively. Conclusion: COL10A1, GKN2 and LIPF are very promising serum markers for the diagnosis of gastric cancer. The joint detection of the serum levels of these three novel markers and PGI and PGII has important value for the early detection of gastric cancer.